Edukasi Kesiapsiagaan Bencana Meningkatkan Pemahaman Prosedur Penyelamatan Diri - Telly Rosdiyani (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Teneng village, Cinangka village has an area of 711,110 Ha. The land is intended for the land of public, social, residential, agricultural, plantation and most land for fisheries because the geographical location of the Cinangka village is close to the coast. This area is including potential earthquake and even tsunami. From this basis, the aim of the Community Service Program is to provide a real life rescue education program to improve the understanding of village community skills in disaster preparedness. The partner of this activity is the Regional Disaster Management Agency (BPBD), the problem faced is that the public does not know the correct procedures for self-rescue against disasters, has not been able to control the panic of a sudden and impending disaster. The method of implementing this service is through (1) Surveying through observation, interviews, and analysis of village problems and potentials, (2) Counseling and simulation of disaster response. The result of this program is to increase the community's knowledge and skills regarding disaster preparedness and to be able to exercise self-control from the fear of disasters to be able to reduce disaster victims. The program is also expected to facilitate the community of information and skills in disaster preparedness.